Air entrainment and oxygen transfer in a venturi - Baylar, A; Emiroglu, ME (Thomas Telford Services Ltd, 2003)
The dissolved oxygen content is a prime indicator of the quality of water. Water jets can increase dissolved oxygen levels when the jet impact velocity exceeds a critical velocity. In this paper, air entrainment rate and oxygen transfer efficiency of a venturi device with air holes at the throat portion were studied experimentally, and in particular the effect of varying numbers, positions, and the open/closed status of the air holes. A negative pressure drew air in through holes at the throat portion of the venturi device. The resulting aeration of the jet affected its expansion, its shape, the air entrainment rate, the bubble penetration depth, and hence the oxygen transfer efficiency. It was demonstrated that the values of the air entrainment rate and the oxygen transfer efficiency of the venturi device were significantly higher than those for a circular nozzle.
Keywords: environment; water supply